The Effectiveness of Using Instagram in Increasing Public Trust Among Followers of Cita Entertainment's Account - Nurdin, Ali; Qoimah, Al Hidayahtul Mus; Rohmah, Nurliya Ni'matul (Al-I'lam: Jurnal Komunikasi dan Penyiaran Islam, 2024)
Abstract:This study aims to evaluate the effectiveness of using Instagram in enhancing public trust among followers of the Cita Entertainment account. The method used is descriptive quantitative, applying the EPIC Model theory, which includes four elements: empathy, persuasion, impact, and communication. The variables examined consist of Instagram usage and the increase in public trust. Data were obtained through an online survey involving followers of the Cita Entertainment account as respondents. The analysis results show that Instagram usage significantly contributes to the increase in public trust. The aspects of empathy and communication have the greatest influence in building trust, while persuasion and impact also contribute positively. In conclusion, effective content strategies on Instagram can enhance public trust, making the platform an important tool for Cita Entertainment in building stronger relationships with its followers. This study recommends the continuous use of the EPIC Model approach to maximize public trust through social media.Abstrak:Penelitian ini bertujuan untuk mengevaluasi efektivitas penggunaan Instagram dalam meningkatkan kepercayaan publik pada pengikut akun Cita Entertainment. Metode yang digunakan adalah kuantitatif deskriptif dengan menerapkan teori EPIC Model yang mencakup empat elemen: Empati, Persuasi, Dampak, dan Komunikasi. Variabel yang diteliti terdiri dari penggunaan Instagram dan peningkatan kepercayaan publik. Data diperoleh melalui survei online yang melibatkan pengikut akun Cita Entertainment sebagai responden. Hasil analisis menunjukkan bahwa penggunaan Instagram berkontribusi signifikan terhadap peningkatan kepercayaan publik. Aspek empati dan komunikasi memiliki pengaruh terbesar dalam membangun kepercayaan, sementara persuasi dan dampak juga memberikan kontribusi positif. Kesimpulannya, strategi konten yang efektif di Instagram dapat meningkatkan kepercayaan publik, sehingga platform ini dapat dijadikan alat penting bagi Cita Entertainment dalam membangun hubungan yang lebih kuat dengan pengikutnya. Penelitian ini menyarankan penggunaan pendekatan EPIK Model secara berkelanjutan untuk memaksimalkan kepercayaan publik melalui media sosial.